The Effect of Quality Costs on Damaged Products in CV. Aneka Ilmu of Pematangsiantar - Tarigan, Vitryani; Saragih, Marintan (Program Studi Akuntansi Universitas Simalungun, 2025)
Every company is required to participate in competition. One of the efforts made by companies to remain competitive is by improving the quality of their production results. Improved quality will reduce the occurrence of defective products, thereby increasing profits. This study aims to determine whether there is an influence of quality costs on defective products at CV. Aneka Ilmu Pematangsiantar. The object of this research is CV. Aneka Ilmu Pematangsiantar. The variables examined are quality costs (prevention costs and appraisal costs) and defective products. Data were collected using the documentation method, and the obtained data were analyzed descriptively and quantitatively. Based on the results of the study, it can be concluded that quality costs are a valuable investment in minimizing defective products at CV. Aneka Ilmu Pematangsiantar. The significant relationship between quality costs and defective products should be considered by company management to achieve overall better product quality, thus reducing the occurrence of defective products